Boda-boda Injuries a Health Problem and a Burden of Disease in Uganda: a Tertiary Hospital Survey - Galukande, Moses; Jombwe, J.; Fualal, J.; Gakwaya, A. (East and central African journal of surgery, 2009)
Injury and deaths due to road traffic crashes are a major public health problem in developing countries. Boda bodas (motorcycles) are a practical and a sought after economic activity in Uganda’s capital and cities. The injuries related to boda bodas contribute significantly to the number road traffic injuries seen at Mulago hospitals, taking out significant resources including consumables and the health worker time. This study investigated the pattern of injuries, mortality and estimate cost of care. Methods: A prospective descriptive observational study over a 9 months period was carried out at Mulago Hospital and Complex, Accident and Emergency wards. The Study population was patients involved in Boda Boda related road traffic crushes. Consecutive patients presenting on every 3rd day were selected. Research Ethics committee approval was sought before the study was commenced. Results: A total of 124 patients presented with injuries that warranted at least an overnight stay at the Accident and Emergency ward. Out of the just over 2000 admissions, the majority were males (sex ratio F: M 1:3.5) There was one fatality. Injuries were in 7 categories namely Head, chest, abdominal, pelvic, spinal and soft tissues and extremity fractures. Helmet use in this study was 22%, an improvement from previous nearly zero percent. The estimated cost of care per injured patient was USD 300. Conclusion: Boda Bodas continue to be a major cause or agent of road traffic injuries and a significant economic burden. The morbidity and mortality can be mitigated by encouraging use of protective gear like helmets and encouraging enforcement of traffic laws.
Keywords: Boda-boda Injuries; Health Problem; Burden of Disease; Uganda